Strength, durability and finite element analysis of hybrid jute/basalt fiber reinforced polymer confined concrete column under axial compression - D. Akhil Varma; Lakshmi Joseph; Mini K. Madhavan; Karingamanna Jayanarayanan; Alessandro Pegoretti (Results in Engineering, 2024)
Implementing retrofitting measures for a civil structure may guarantee its ongoing safety and operation, while also extending its lifespan. The present investigation focused on the examination of compressive axial loads on concrete columns that were confined by natural fiber reinforced polymer (FRP). In particular, concrete cylinders confined with jute and basalt fiber epoxy composites were evaluated for their strength and durability. Various strength tests were conducted on unconfined and, jute, basalt, and hybrid jute-basalt FRP confined concrete cylinders with varying thicknesses of the FRP layers. Effectiveness of these natural FRP systems in providing external confinement to concrete columns in various environmental conditions were investigated, including exposure to acidic, alkaline, seawater, and potable water environments. Test results demonstrated that external confinement with hybrid FRP wraps, i.e. with both jute and basalt fibers, enhanced the load-bearing and energy absorption capacities by 63.64 % and 287 %, respectively. The confinement effectiveness of FRP wrapped specimens were 213 %, 164 %, 166 % and 163 % respectively compared to the unconfined specimens after exposure to acidic, alkaline, seawater and potable water environments. These impressive outcomes may be ascribed to the intrinsic rigidity of hybrid fibers. Furthermore, a finite element analysis (FEA) model of FRP confined concrete columns was performed using ABAQUS software calibrated with the experimental data. A close agreement between the experimental results and the adopted numerical model was observed. The outcome of the study suggests that the confinement with natural FRP can be used as a prominent retrofitting technique for columns in a variety of environments which can thus enhance the durability and sustainability of civil constructions.